Long-Term Effects of COVID-19 and the Pandemic on Tinnitus Patients - Erinc, Murat; Mutlu, Ahmet; Celik, Serdal; Kalcioglu, Mahmut Tayyar; Szczepek, Agnieszka J. (Frontiers in Neurology, 2022)
This study aimed to explore the effect of COVID-19 and the pandemic period on the tinnitus-related complaints of patients with chronic tinnitus. Ninety-six patients diagnosed with chronic tinnitus before pandemics were enrolled in this study. All patients filled the Tinnitus Handicap Inventory (THI), the Visual Analogue Scale (VAS) on the effects of tinnitus, and the Hyperacusis Questionnaire (HQ) before the pandemic and in January 2022. Thirty-seven of 96 patients contracted COVID-19 between March 2020 and January 2022. These patients were further asked about leading COVID-19 symptoms, changes in tinnitus complaints during and after the disease, and whether their hearing abilities were affected. More than eight percent of patients in the COVID-19 group confirmed worsening their hearing ability. No decrease in the tinnitus complaint during COVID-19 was noted; 24.3% of the patients reported exacerbation of tinnitus, and 75.7% said tinnitus remained the same. In the COVID-19-negative group, 13.5% reported tinnitus decrease during the pandemic, 57.6% said it remained the same, and 28.8% reported exacerbation of tinnitus. Among the COVID-19-positive patients, there was a significant increase in tinnitus loudness, tinnitus effect on concentration, and THI scores. In contrast, in COVID-19-negative patients, hyperacusis worsened significantly (p <0.05). This study indicates different effects of the infection with SARS-Cov-2 and the pandemic period on patients with chronic tinnitus. It also provides evidence for tinnitus worsening among the infected patients as a possible long-term effect of COVID-19.